The Development of Postoperative Hydrocephalus following Midline Posterior Cranial Fossa Tumors with Hydrocephalus Surgery with Preoperative Ventriculoperitoneal (V-P) shunt in Pediatric Patients - Soumen Samadder; Shuvra Mandol; D M Arman; Sudipta Kumer Mukherjee; Moududul Haque; Md Motasimul Hasan (Bangladesh Journal of Neurosurgery, 2024)
Background: Posterior cranial fossa tumors are the most common tumors in children and constitute about two-thirds of pediatric brain tumors. Such pediatric patient presents with symptoms and signs of raised intracranial pressure. All pediatric patients were diagnosed with midline posterior cranial fossa tumors with hydrocephalus. The ventriculoperitoneal shunt was done before definitive surgery for all patients. Definitive surgery was done later on. These patients were followed up to the 7th postoperative day following definitive surgery. We assessed the development of postoperative hydrocephalus. Objectives: The objective of the study was to assess the development of postoperative hydrocephalus of midline posterior cranial fossa tumors with hydrocephalus after definitive surgery following ventriculoperitoneal (V-P) shunt in pediatric patients. Methods: This cross-sectional experimental study was conducted in the Department of Neurosurgery, Bangabandhu Sheikh Mujib Medical University, and the Department of Pediatrics Neurosurgery, National Institute of Neurosciences & Hospital, Dhaka from March 2018 to September 2019. A total of 43 pediatric patients were included in this study. All pediatric patients were diagnosed with midline posterior cranial fossa tumors with hydrocephalus. The ventriculoperitoneal shunt was done before definitive surgery. Later on, definitive surgery was performed. Follow-up of these patients was done up to the 7th postoperative day. The development of postoperative hydrocephalus was observed. Data were processed and then analyzed. Demographic data were expressed in numbers and percentages. The development of postoperative hydrocephalus was expressed in number and percentage. Logistic regression was done to predict the relationship between the dependent variable (development of hydrocephalus) and independent variables (age, sex, and the extent of tumor removal). The odds ratio (OR) was calculated by using the Chi-square test. The chi-square test gave a Wald statistic by observing at the 95% CI of the odds ratio. Statistical significance was set to p-value <0.05. Results: A total of 43 pediatric patients were included in the study from March 2018 to September 2019. In the study, the maximum patients were in the age group 11-15 years. The mean age of the patients was 8.25 years ± 4.14. The male-to-female ratio was 1.26:1. The study showed preoperative clinical features which includes headache 40 (93%), vomiting 37 (86%), visual disturbance 24 (55.8%), altered level of consciousness 3 (7.0%), gait disturbance 30 (69.8%), swallowing disturbance 9 (20.9%), papilledema 38 (88.4%), lower cranial nerves palsy 8 (18.6%). Among them, 25 patients developed postoperative complications after definitive surgery. Development of postoperative hydrocephalus was found in 2 (4.65%) patients. Logistic regression was found to be statistically non-significant in this study. Conclusion: The development of postoperative hydrocephalus of midline posterior cranial fossa tumors with hydrocephalus after definitive surgery following ventriculoperitoneal (V-P) shunt in pediatric patients was not the major complication among others. Bang. J Neurosurgery 2024; 13(2): 86-95